Modelling of foreign trade in applied general equilibrium models - Koschel, Henrike,Schmidt, Tobias F. N. (ZEW, 1998)
The specification of the world closure, i.e. the way of closing the domestic economy model by incorporating the external sector, is a crucial component for those models in which production and consumption is not specified endogenously for all countries. This paper looks explicitly at the assumptions concerning the trade behaviour of the rest of the world that can be found in literature and in empirical applications, such as the GEM-E3 General Equilibrium Model for the EU. Starting from a description of the closure rule in the actual GEM-E3 model version, two main changes in the foreign trade specification are proposed and tested using an EU-wide ecological tax reform scenario. The first change refers to the rest of the world's export supply function in which a constant finite price elasticity is introduced. The second change concerns the rest of the world's import demand function in which an activity variable is incorporated. In summary, the impact in terms of economic welfare and changes in macroeconomic variables is noteworthy for the former case while no substantial changes could be observed for the latter case. Additionally, the sensitivity of the GEM-E3 model to variations in key parameter values such as the upper-level Armington elasticity are analysed. Results indicate that the model can be interpreted as quite robust to parameter changes.
Keywords: Arbeitspapier; Graue Literatur; Buch; Allgemeines Gleichgewicht; Internationale Wirtschaft; Offene Volkswirtschaft; Umweltökonomik; Ökosteuer; Steuerreform; Theorie; EU-Staaten